Potential Factors related to COVID-19 Vaccine Hesitancy in Indonesia: A Literature Review - Kevin Kristian; Anisya Lutfia Andini; Fransiska Eka Putri; Julian; Karina Sylvana; Kenji Sungkhar; Mentari Artanti Jelita; Mikhael Aditya (Journal of Urban Health Research, 2023)
Introduction: The pandemic of COVID-19 has become a burden to the world's health system, in which strategic measures are needed, especially vaccination. However, numbers of challenge have been reported regarding the so-called most effective public health intervention, such as vaccine hesitancy. On top of that, WHO has acknowledged vaccine hesitancy in the top list of 10 most dangerous threats to global health. The spectrum related to the reluctance to receive vaccination in society has also occurred in previous infectious diseases management and during the COVID-19 pandemic. This review aimed to identify factors and mechanism related to COVID-19 vaccine hesitancy in Indonesia. Method: This study provided a review of 14 literatures from 2019 to 2021 using ProQuest and Google Scholar discovered through the selected keywords. The SAGE WG model for vaccine hesitancy framework was used as the main reference in identifying and explaining the associated factors of phenomenon. Results: Based on the analysis of framework, determinants related to confidence crucial in affecting the acceptance level of COVID-19 vaccine in the community. In regard to that aspect, various factors within the scope of individual and social influences, vaccine and vaccination-specific issues, as well as contextual influences may well-explained the plausible mechanism that build hesitancy over vaccination. Accordingly, this study found that mistrust and skepticism related to the effectiveness of vaccine, safety concerns, and adverse reactions discouraged people from getting vaccinated. Furthermore, religious matters such as unavailable halal certification, along with poor socioeconomical factors, and misinformation that were spread through the media also prevent people to receive COVID-19 vaccine and risk the development of herd-immunity toward COVID-19 in the community. Conclusions: Various factors were identified regarding the development of vaccine hesitancy in Indonesia. Understanding the plausible factors and mechanism that prevented people to get COVID-19 vaccine are substantial to strategically address the phenomenon and successfully manage the COVID-19 pandemic in Indonesia. Keywords: COVID-19 – Indonesia - vaccine hesitancy – asia – outbreak - prevention